Working with the Dataverse Repository: A training provided to the Ethiopian Nutrition Information Platform for Nutrition - Habte, Yetimwork (2019)
This presentation introduces the basics of the Dataverse including preparing the submission to the Dataverse, creating an account and logging in, adding datasets to the Dataverse account, and metadata.